2022
DOI: 10.3390/nano12040639
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport in Iron Phosphate-Based Glass-(Ceramics): Insights into the Role of B2O3 and HfO2 from Model-Free Scaling Procedures

Abstract: In this work, we report the effect of the addition of modifiers and network formers on the polaronic transport in iron phosphate glasses (IPG) in two systems of HfO2–B2O3–Fe2O3–P2O5, to which up to 8 mol% boron and hafnium are added. The addition of oxides significantly changes the Fe2+/Fetotal ratio, thus directly affecting the polaron number density and consequently controlling DC conductivity trends for both series studied by impedance spectroscopy. Moreover, we found that short-range polaron dynamics are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…An example of such a system are the Na-Mo-P GCs from our prior research, where it was demonstrated that specifically the samples with a porous microstructure exhibit outstanding humidity-sensing capabilities [26]. Building upon our research group's prior work, which demonstrated the efficacy of Solid-State Impedance Spectroscopy (SS-IS) for the comprehensive analysis of electrical and dielectric properties in phosphate-based glasses [27][28][29][30] and GC materials [26,[31][32][33][34], including its utility in studying dielectric relaxation phenomena, assessing the dielectric loss factor, and distinguishing between bulk and grain boundary contributions, we have chosen to investigate the electrical and dielectric properties of GCs prepared from the 40Na2O-xGeO2-(60-x)P2O5 glass system described in [29].…”
Section: Introductionmentioning
confidence: 99%
“…An example of such a system are the Na-Mo-P GCs from our prior research, where it was demonstrated that specifically the samples with a porous microstructure exhibit outstanding humidity-sensing capabilities [26]. Building upon our research group's prior work, which demonstrated the efficacy of Solid-State Impedance Spectroscopy (SS-IS) for the comprehensive analysis of electrical and dielectric properties in phosphate-based glasses [27][28][29][30] and GC materials [26,[31][32][33][34], including its utility in studying dielectric relaxation phenomena, assessing the dielectric loss factor, and distinguishing between bulk and grain boundary contributions, we have chosen to investigate the electrical and dielectric properties of GCs prepared from the 40Na2O-xGeO2-(60-x)P2O5 glass system described in [29].…”
Section: Introductionmentioning
confidence: 99%